Mental health literacy and seeking for professional help among secondary school students in Slovakia: a brief report - Sokolová, Lenka (Frontiers in Public Health, 2024)
Secondary school students are at risk for mental health problems, especially nowadays, when we face an increase in mental health issues among adolescents and the general population. Mental health literacy (MHL) and help-seeking behavior are considered protective factors; however, we lack data on the levels of MHL in secondary school students and how MHL is developed in schools. This correlational and comparative study was designed to investigate mental health literacy (MHL) and help-seeking behavior among secondary school students in Slovakia. A convenient sample of 250 Slovak secondary school students responded to an anonymous online survey consisting of two scales (Mental Health Literacy Scale and Self-stigma of Seeking Help). Significant differences in mental health literacy (t(248) = 5.56; p ≤ 0.0) and stigma of seeking help (t(248) = −4.33; p ≤ 0.01) were observed between students in general and vocational secondary school. Students in general secondary school who attended optional psychology courses had the highest scores in mental health literacy (U = 987; p = 0.003). These preliminary findings showed that secondary students with a higher level of mental health literacy reported a lower level of self-stigmatization related to seeking professional mental health help (r = −0.339; p ≤ 0.01). Implementing mental health education into secondary school curricula can potentially help increase mental health literacy and decrease self-stigma of seeking help.